AI as Creator Debate: A Comparative Study of Regulations in Indonesia and the UK - Alief Qurratul 'Ain Musafa' (Sinergi International Journal of Law, 2026)
The concept of creator in copyright law, which has historically been associated with human creativity, is called into question by the growth of (Artificial Intelligence) in the creation of creative works. This essay discusses three primary subjects: (1) how AI regulation is governed by Indonesian law; (2) how AI regulation is governed by English law; and (3) what kind of legal protection is available for works created by AI. The purpose of this study is to examine how each legal system handles works created by artificial intelligence, particularly with regard to identifying creators and copyright protection procedures. By examining Law Number 28 of 2014 governing copyright in Indonesia and the Copyright, Designs and Patents Act (CDPA) 1988 in the UK, normative legal research with a comparative perspective is employed. The study's findings demonstrate that Indonesian law still bases creator recognition on human creative contributions. In contrast, the UK does not recognize AI as a legal subject and instead grants creator status to the entity who makes the required arrangements for the creation process. This comparison highlights the fact that attribution of rights to the human creators who oversee the creative process can accomplish acknowledgment of AI works without necessarily requiring recognition of the AI as creator. This essay suggests a more flexible normative approach to AI-generated works in order to improve Indonesian copyright law.The concept of creator in copyright law, which has historically been associated with human creativity, is called into question by the growth of (Artificial Intelligence) in the creation of creative works. This essay discusses three primary subjects: (1) how AI regulation is governed by Indonesian law; (2) how AI regulation is governed by English law; and (3) what kind of legal protection is available for works created by AI. The purpose of this study is to examine how each legal system handles works created by artificial intelligence, particularly with regard to identifying creators and copyright protection procedures. By examining Law Number 28 of 2014 governing copyright in Indonesia and the Copyright, Designs and Patents Act (CDPA) 1988 in the UK, normative legal research with a comparative perspective is employed. The study's findings demonstrate that Indonesian law still bases creator recognition on human creative contributions. In contrast, the UK does not recognize AI as a legal subject and instead grants creator status to the entity who makes the required arrangements for the creation process. This comparison highlights the fact that attribution of rights to the human creators who oversee the creative process can accomplish acknowledgment of AI works without necessarily requiring recognition of the AI as creator. This essay suggests a more flexible normative approach to AI-generated works in order to improve Indonesian copyright law.